Analisis Pendekatan Data Pemakaian Kanal Radio Hf - Sutoyo Sutoyo; M Amaluddin (UIN Sultan Syarif Kasim Riau, 2015)
High Frequency ( HF ) radio waves that have a wavelength of 10 meters to 100 meters , and works at a frequency of 3 MHz to 30 MHz . One channel utilization maritime HF as used for voice communications.The availability of bandwidth on maritime band channel can be maximized its use for voice communications , the necessary analysis of the availability of channels through the use of data results in data communications. This research analyzes the data distribution approach that includes the use of the approach through the channel distribution model for data communications in order to optimally when used . From the data processing provided and the frequency is the mean availability of time at a frequency 6.401 MHz and 6.404 MHz at 6407 MHz while the frequency is different . The mean frequency of 6,401 MHz obtained 412 911 millisecond time availability with a lot of data for 24 643 data. The mean frequency of 6404 MHz obtained 412 911 millisecond time availability of data at 25348 with lots of data. The mean frequency of 6,407 MHz obtained 483 849 millisecond time availability of data at 25438 with lots of data. Model availability of time for communication of data is exponential models for the exponential distribution MSE smaller than other distributions.Keyword : band maritime, channel availability, HF radio, the model